Hipnosis Lima Jari dengan Pendekatan Spiritual Menurunkan Insomnia pada Lansia - Dudi Hartono; Iwan Somantri; Sofia Februanti (Politeknik Kesehatan Tanjung Karang, 2019)
Sleep needs are basic human needs, including the elderly. However, many elderly people have difficulty sleeping (insomnia). This study aimed to determine the effect of a five-finger spiritual hypnosis approach to insomnia experienced by the elderly. The study design used a quasi-experiment, with one group pretest-posttest design approach without a control group. Sampling using purposive sampling technique, with a total of 34 people. Elderly is assigned to do a 5-finger hypnosis technique with a spiritual approach independently every night before going to bed for up to three nights. Data analysis using univariate and bivariate. The results showed that after the elderly were intervened in the form of five-finger hypnosis with a spiritual approach for 3 days, there was an influence on the incidence of insomnia in the elderly p-value=0,000 (p<0.05). Five-finger hypnosis with a spiritual approach can reduce the incidence of insomnia in the elderly.